IICA strategy for Bahamas : 2014-2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The Inter-American Institute for Cooperation on Agriculture's Bahamas office is pleased to present the country strategy for the year 2015 – 2018. The IICA Country Strategy for the Bahamas will serve as a guide to channel the technical cooperation provided by the office over the next four years. The country strategy reflects the needs of the agricultural sector, gathered through a consultative process with stakeholders in the agricultural sector, documents and publications and communications produced and released with main stakeholders. The stakeholders include the Ministry of Agriculture and Marine Resources (MAMR), the Bahamas Agricultural and Industrial Corporation (BAIC), The Bahamas Agriculture and Marine Science Institute (BAMSI) and other institutions of the public and private sector.